Rational Control of Off‐State Heterogeneity in a Photoswitchable Fluorescent Protein Provides Switching Contrast Enhancement. Issue 19 (12th August 2022) - Adam, Virgile; Hadjidemetriou, Kyprianos; Jensen, Nickels; Shoeman, Robert L.; Woodhouse, Joyce; Aquila, Andrew; Banneville, Anne‐Sophie; Barends, Thomas R. M.; Bezchastnov, Victor; Boutet, Sébastien; Byrdin, Martin; Cammarata, Marco; et al.
Abstract: Reversibly photoswitchable fluorescent proteins are essential markers for advanced biological imaging, and optimization of their photophysical properties underlies improved performance and novel applications. Here we establish a link between photoswitching contrast, one of the key parameters that dictate the achievable resolution in nanoscopy applications, and chromophore conformation in the non‐fluorescent state of rsEGFP2, a widely employed label in REversible Saturable OpticaL Fluorescence Transitions (RESOLFT) microscopy. Upon illumination, the cis chromophore of rsEGFP2 isomerizes to two distinct off ‐state conformations, trans1 and trans2, located on either side of the V151 side chain. Reducing or enlarging the side chain at this position (V151A and V151L variants) leads to single off ‐state conformations that exhibit higher and lower switching contrast, respectively, compared to the rsEGFP2 parent. The combination of structural information obtained by serial femtosecond crystallography with high‐level quantum chemical calculations and with spectroscopic and photophysical data determined in vitro suggests that the changes in switching contrast arise from blue‐ and red‐shifts of the absorption bands associated to trans1 and trans2, respectively. Thus, due to elimination of trans2, the V151A variants of rsEGFP2 and its superfolding variant rsFolder2 display a more than two‐fold higher switching contrast than their respective parent proteins, both in vitro and in E. coli cells. The application of the rsFolder2‐V151A variant is demonstrated in RESOLFT nanoscopy. Our study rationalizes the connection between structural and photophysical chromophore properties and suggests a means to rationally improve fluorescent proteins for nanoscopy applications. Abstract : The chromophore of the reversibly photoswitchable fluorescent protein rsEGFP2 can adopt two conformations, trans1 (yellow model) and trans2 (orange), in the non‐fluorescent off‐state. The trans1 conformation is characterized by a blue‐shifted absorption spectrum, whose decreased overlap with the spectrum of the fluorescent on‐state (green) leads to increased switching contrast in Reversible saturable optical fluorescence transitions (RESOLFT) nanoscopy.